Considering the biology of late recurrences in selecting patients for extended endocrine therapy in breast cancer. (November 2018) - Bense, Rico D.; Qiu, Si-Qi; de Vries, Elisabeth G.E.; Schröder, Carolien P.; Fehrmann, Rudolf S.N.
Highlights: Extending 5 years of tamoxifen with 5 years of tamoxifen or AI reduces late recurrence risk by 2–5%, but results of extending AI-based therapy are inconsistent. Multiple tools predict late recurrence risk, but not necessarily benefit from extended endocrine therapy. Tools for predicting benefit from extended endocrine therapy are sparse. Patients with high expression of estrogen-responsive genes in the primary tumor might benefit most from extended endocrine therapy. Abstract: Extended endocrine therapy can reduce recurrences occurring more than 5 years after diagnosis (late recurrences) in estrogen receptor (ER)-positive breast cancer. Given the side effects of endocrine therapy, optimal patient selection for extended treatment is crucial. Enhanced understanding of late recurrence biology could optimize patient selection in this setting. We therefore summarized the current knowledge of late recurrence biology, clinical trials on extended endocrine therapy, and tools for predicting late recurrence and benefit from treatment extension. Extending 5 years of tamoxifen therapy with 5 years of tamoxifen or an aromatase inhibitor (AI) reduces late recurrence risk by 2–5%, but results of extending AI-based therapy are inconsistent. Although several clinicopathological parameters and multigene assays are prognostic for late recurrence, selection tools predicting benefit from extended endocrine therapy are sparse. Therefore, we additionally performed a pooled analysis using 2231 mRNA profiles of patients with ER-positive/human epidermal growth factor receptor 2-negative breast cancer. Gene Set Enrichment Analysis was applied on genes ranked according to their association with early and late recurrence risk. Higher expression of estrogen-responsive genes was associated with a high recurrence risk beyond 5 years after diagnosis when patients had received no systemic therapy. Although 5 years of endocrine therapy reduced this risk, this effect disappeared after treatment cessation. This suggests that late recurrences of tumors with high expression of estrogen-responsive genes are likely ER-driven. Long-term intervention in this pathway by means of extended endocrine therapy might reduce late recurrences in patients with tumors showing high expression of estrogen-responsive genes.